Effect of pH on Thermoanaerobacterium thermosaccharolyticum DSM 571 growth, spore heat resistance and recovery. (May 2016) - Mtimet, Narjes; Guégan, Stéphanie; Durand, Lucile; Mathot, Anne-Gabrielle; Venaille, Laurent; Leguérinel, Ivan; Coroller, Louis; Couvert, Olivier
Abstract: Thermophilic spore-forming bacteria are potential contaminants in several industrial sectors involving high temperatures (40–65 °C) in the manufacturing process. Among those thermophilic spore-forming bacteria, Thermoanaerobacterium thermosaccharolyticum, called "the swelling canned food spoiler", has generated interest over the last decade in the food sector. The aim of this study was to investigate and to model pH effect on growth, heat resistance and recovery abilities after a heat-treatment of T. thermosaccharolyticum DSM 571. Growth and sporulation were conducted on reinforced clostridium media and liver broth respectively. The highest spore heat resistances and the greatest recovery ability after a heat-treatment were obtained at pH condition allowing maximal growth rate. Growth and sporulation boundaries were estimated, then models using growth limits as main parameters were extended to describe and quantify the effect of pH on recovery of injured spores after a heat-treatment. So, cardinal values were used as a single set of parameters to describe growth, sporulation and recovery abilities. Besides, this work suggests that T. thermosaccharolyticum preserve its ability for germination and outgrowth after a heat-treatment at a low pH where other high resistant spore-forming bacteria like Geobacillus stearothermophilus are unable to grow. Highlights: Thermoanaerobacterium thermosaccharolyticum growth cardinal values were estimated. Highest heat resistance was obtained for spores produced at optimal growth pH. Recovery abilities after a heat-treatment were enhanced at a pH between 5.50 and 6.50. A model using growth limits was validated on an anaerobic spore-forming bacterium.